Revisiting the physiological roles of SGLTs and GLUTs using positron emission tomography in mice. (10th May 2016) - Sala‐Rabanal, Monica; Hirayama, Bruce A.; Ghezzi, Chiara; Liu, Jie; Huang, Sung‐Cheng; Kepe, Vladimir; Koepsell, Hermann; Yu, Amy; Powell, David R.; Thorens, Bernard; Wright, Ernest M.; Barrio, Jorge R.
Abstract : Key points: Glucose transporters are central players in glucose homeostasis. There are two major classes of glucose transporters in the body, the passive facilitative glucose transporters (GLUTs) and the secondary active sodium‐coupled glucose transporters (SGLTs). In the present study, we report the use of a non‐invasive imaging technique, positron emission tomography, in mice aiming to evaluate the role of GLUTs and SGLTs in controlling glucose distribution and utilization. We show that GLUTs are most significant for glucose uptake into the brain and liver, whereas SGLTs are important in glucose recovery in the kidney. This work provides further support for the use of SGLT imaging in the investigation of the role of SGLT transporters in human physiology and diseases such as diabetes and cancer. Abstract: The importance of sodium‐coupled glucose transporters (SGLTs) and facilitative glucose transporters (GLUTs) in glucose homeostasis was studied in mice using fluorine‐18 labelled glucose molecular imaging probes and non‐invasive positron emission tomography (PET) imaging. The probes were: α‐methyl‐4‐[F‐18]‐fluoro‐4‐deoxy‐d ‐glucopyranoside (Me‐4FDG), a substrate for SGLTs; 4‐deoxy‐4‐[F‐18]‐fluoro‐d ‐glucose (4‐FDG), a substrate for SGLTs and GLUTs; and 2‐deoxy‐2‐[F‐18]‐fluoro‐d –glucose (2‐FDG), a substrate for GLUTs. These radiolabelled imaging probes were injectedi.v. into wild‐type, Sglt1 –/–, Sglt2 –/– and Glut2 –/– mice and their dynamic whole‐body distribution was determined using microPET. The distribution of 2‐FDG was similar to that reported earlier (i.e. it accumulated in the brain, heart, liver and kidney, and was excreted into the urinary bladder). There was little change in the distribution of 2‐FDG in Glut2 –/– mice, apart from a reduction in the rate of uptake into liver. The major differences between Me‐4FDG and 2‐FDG were that Me‐4FDG did not enter the brain and was not excreted into the urinary bladder. There was urinary excretion of Me‐4FDG in Sglt1 –/– and Sglt2 –/– mice. However, Me‐4FDG was not reabsorbed in the kidney in Glut2 –/– mice. There were no differences in Me‐4FDG uptake into the heart of wild‐type, Sglt1 –/– and Sglt2 –/– mice. We conclude that GLUT2 is important in glucose liver transport and reabsorption of glucose in the kidney along with SGLT2 and SGLT1. Complete reabsorption of Me‐4FDG from the glomerular filtrate in wild‐type mice and the absence of reabsorption in the kidney in Glut2 –/– mice confirm the importance of GLUT2 in glucose absorption across the proximal tubule. Key points: Glucose transporters are central players in glucose homeostasis. There are two major classes of glucose transporters in the body, the passive facilitative glucose transporters (GLUTs) and the secondary active sodium‐coupled glucose transporters (SGLTs). In the present study, we report the use of a non‐invasive imaging technique, positron emission tomography, in mice aiming to evaluate the role of GLUTs and SGLTs in controlling glucose distribution and utilization. We show that GLUTs are most significant for glucose uptake into the brain and liver, whereas SGLTs are important in glucose recovery in the kidney. This work provides further support for the use of SGLT imaging in the investigation of the role of SGLT transporters in human physiology and diseases such as diabetes and cancer.